The Possibility of Altruism - Nagel, Thomas, 1937- (Book collections on Project MUSE., 2016)
Just as there are rational requirements on thought, there are rational requirements on action. This book defends a conception of ethics, and a related conception of human nature, according to which altruism is included among the basic rational requirements on desire and action.